The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/02755947.2012.662089
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Economic Values of Trout Anglers and Nontrout Anglers in Colorado's Stocked Public Reservoirs

Abstract: Trout are often popular target species for anglers worldwide and have been the most commonly stocked game fish species in the USA. Using survey data collected at Colorado's stocked public reservoirs in 2009, we found that trout anglers’ net economic benefits were more than twice those of anglers fishing for species other than trout. Values estimated from the travel cost method produced angler‐day consumer surpluses (willingness to pay [WTP]) of US$191.60 for trout anglers and $61.68 for nontrout anglers. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Overall, we found that Chinook Salmon, Coho Salmon, and steelhead are the most valuable fish to Great Lakes anglers in Michigan. Trout and salmon fisheries are known to be popular among recreational anglers (Loomis and Ng 2012), and prior studies have identified Coho Salmon, followed by steelhead and Chinook Salmon, as the most valuable fish in the Great Lakes (Johnston et al 2006). Our results also indicate that these are the most valuable species, although we consistently estimated Chinook Salmon as being more valuable than Coho Salmon, which may reflect changing preferences among Great Lakes anglers.…”
Section: Discussionsupporting
confidence: 46%
“…Overall, we found that Chinook Salmon, Coho Salmon, and steelhead are the most valuable fish to Great Lakes anglers in Michigan. Trout and salmon fisheries are known to be popular among recreational anglers (Loomis and Ng 2012), and prior studies have identified Coho Salmon, followed by steelhead and Chinook Salmon, as the most valuable fish in the Great Lakes (Johnston et al 2006). Our results also indicate that these are the most valuable species, although we consistently estimated Chinook Salmon as being more valuable than Coho Salmon, which may reflect changing preferences among Great Lakes anglers.…”
Section: Discussionsupporting
confidence: 46%
“…This is clearly described by Weiler (2006), Prayaga et al (2006), Taylor, Mckean, & Johnson (2010), Mckean, Johnson, & Taylor (2012), and Hendarto, Al-Hasan, Yumantoko, & Nur (2018). Consequently, this study eliminates time cost from the model, which is similar to the study conducted by Prayaga et al (2006) and Loomis & Ng (2012).…”
Section: Discussionmentioning
confidence: 56%
“…The magnitude of Northern Pike predation influences salmonid management initiatives and is likely a primary factor contributing to reduced Rainbow Trout abundance and return to anglers. Efforts to reduce costs by eliminating Rainbow Trout stocking could have negative impacts on angler satisfaction (Loomis and Ng 2012) and may have unintended consequences for other salmonids (i.e., Lake Trout) in Pactola Reservoir (Scheibel 2015). For instance, in the absence of Rainbow Trout, there could be increased competition for Rainbow Smelt between Lake Trout and Northern Pike, as Northern Pike would likely consume Rainbow Smelt in the absence of Rainbow Trout (Beyerle and Williams 1968;Wahl and Stein 1988;Sepulveda et al 2013).…”
Section: Discussionmentioning
confidence: 99%